Tata Laksana Penanganan Cedera Muskuloskeletal di FKTP Puskesmas Mangulewa - Fulgensius Elpianus Kira; Stanislaus Arkineus Kaju; Robertus Lili Bile (Intellektika : Jurnal Ilmiah Mahasiswa, 2026)
Musculoskeletal injuries are common health problems encountered in sports activities and daily life. Primary Health Care Facilities (PHCF) such as community health centers play an important role in the initial management of musculoskeletal injuries before referral to higher-level health facilities. This study aimed to describe the management of musculoskeletal injuries at the PHCF of UPTD Mangulewa Health Center. The methods used were field observation, structured interviews with health professionals, and simulation of musculoskeletal injury management. The results showed that UPTD Mangulewa Health Center has adequate facilities, equipment, and health personnel for managing musculoskeletal injuries at the primary care level. The management procedures were carried out systematically through anamnesis, physical examination, initial treatment based on RICE principles and immobilization, pharmacological therapy, and an integrated referral system. Fracture management simulations indicated that students gained practical understanding of immobilization techniques and early injury management. In conclusion, the management of musculoskeletal injuries at the PHCF of Mangulewa Health Center is in accordance with primary health care service standards and supports the prevention of injury complications.